2021
DOI: 10.3390/s21051635
|View full text |Cite
|
Sign up to set email alerts
|

Breathable Textile Rectangular Ring Microstrip Patch Antenna at 2.45 GHz for Wearable Applications

Abstract: A textile patch antenna is an attractive package for wearable applications as it offers flexibility, less weight, easy integration into the garment and better comfort to the wearer. When it comes to wearability, above all, comfort comes ahead of the rest of the properties. The air permeability and the water vapor permeability of textiles are linked to the thermophysiological comfort of the wearer as they help to improve the breathability of textiles. This paper includes the construction of a breathable textile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
(40 reference statements)
0
22
0
1
Order By: Relevance
“…Furthermore, the most sophisticated 3D fabric-based textronics are constructed via the insertion of extra oriented conductive yarns into a 2D-shaped substrate. 74 Structurally, 3D textronics maintain higher compactness and deformability compared to 2D textronics and also have signicant potential application in pressure sensing circuits, 75 antennas, 76 thermoelectric powering, 77 and solar cells 78 due to their unique structural integrity. For example, a 2D knitted structure constructed via the we knitting process with the insertion of Ag-coated yarn and nylon spandex could provide strain sensing data for detecting body motions.…”
Section: Preparation Of Fabric-based Textronic Structuresmentioning
confidence: 99%
“…Furthermore, the most sophisticated 3D fabric-based textronics are constructed via the insertion of extra oriented conductive yarns into a 2D-shaped substrate. 74 Structurally, 3D textronics maintain higher compactness and deformability compared to 2D textronics and also have signicant potential application in pressure sensing circuits, 75 antennas, 76 thermoelectric powering, 77 and solar cells 78 due to their unique structural integrity. For example, a 2D knitted structure constructed via the we knitting process with the insertion of Ag-coated yarn and nylon spandex could provide strain sensing data for detecting body motions.…”
Section: Preparation Of Fabric-based Textronic Structuresmentioning
confidence: 99%
“…Work carried out over the past decade have employed ultrawideband (UWB) antenna technology, with its unique features of high-speed data rates, very small signal interference, simple low-cost design, to construct microwave imaging systems [5]. Existing work [9,10] have also explored the use of flexible materials to design the antennas and, thus, it will be suitable for on-body applications. In addition, previous studies demonstrated that incorporating metamaterials (MTMs) into conventional antenna design resulted in enhancement of antenna's gain bandwidth, higher radiation efficiency, improvement in radiation pattern, and reduction of specific absorption rate (SAR) [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The need for more IoT devices has contributed to the development of new antenna topologies with unique shapes made on unconventional substrates. Unconventional substrates, such as polydimethylsiloxane polymer [22,23], natural rubber [24], and textiles [12,20,[25][26][27][28][29][30][31][32], were used to create flexible antennas. Furthermore, for an unobtrusive integration into garments and accessories, several antenna geometries, such as those with buttons [33] or that are optically transparent [34], have a zip-based monopole [35], or are logo-based [36][37][38][39][40][41][42][43][44][45][46][47][48][49], have been reported.…”
Section: Introductionmentioning
confidence: 99%